Accounting for realistic Thermo-Hydro-Mechanical boundary conditions whilst modeling the ageing of concrete in nuclear containment buildings: Model validation and sensitivity analysis. (1st July 2018) - Bouhjiti, D.E.-M.; Boucher, M.; Briffaut, M.; Dufour, F.; Baroth, J.; Masson, B.
Highlights: Suggestion and validation of a weakly coupled Thermo-Hydro-Mechanical modelling strategy of large concrete structures' behaviour. Validation of a revisited drying creep behaviour law under cyclic hydric flux at the specimen and structural scales. Use of realistic in-situ Thermo-Hydro-Mechanical boundary conditions around operating nuclear containment buildings. Application of the developed modelling strategy to the standard zone of a nuclear containment building using Representative Structural Volumes. Analysis of the effects of spatial and temporal variation of Thermo-Hydro-Mechanical boundaries on concrete ageing in nuclear containment buildings. Abstract: The prediction of large concrete structures behavior such as bridges, dams and Nuclear Containment Buildings (NCB) is a key issue with regards to the evaluation of their durability, safety and the safety of their surrounding environment. In this work, a weakly coupled Thermo-Hydro-Mechanical (THM) modeling strategy is presented within the serviceability state of large structures. It aims at (a) defining and predicting the temperature, the relative humidity, the strains and the stresses in ageing concrete structures under variable and realistic THM loads and (b) qualitatively assessing the damage risk using a stress-based criterion. With that aim in view, the effect of concrete drying on its long term behavior is highlighted by using a revisited description of drying creep adapted to variable hydric conditions. The concrete's response to variable THM boundaries is also compared to the one where mean and constant ones are considered in the case of NCBs. Two concrete types and three scales are considered for the THM study: the specimen scale for concrete properties identification, the 1:3 and 1:1 (full) scales of Representative Structural Volumes (RSV) for predictive and structural analyses. Through the FE sensitivity analysis, it is shown that the spatial variation of the temperature along the NCB's height has more effect on the concrete's ageing than its variation in time. Whereas, the temporal variation of hydric boundaries has a negligible effect away from the drying-exposed surfaces. Finally, it is demonstrated that, due to initial prestressing loads, the ageing kinetic within the NCB's wall is heterogeneous and cannot be described using constant prestressing loads. Therefore, it is recommended to account for the spatial THM boundaries' variation when predicting the global concrete ageing in large concrete structures.